Deformation induced atomic-scale frictional characteristics of atomically thin two-dimensional materials. (15th August 2020) - Peng, Yitian; Zeng, Xingzhong; Yu, Kang; Lang, Haojie
Abstract: The deformation induced atomic-scale stick-slip behaviors are unique and prominent friction characteristics of atomically thin two-dimensional (2D) materials. Here, the deformation induced atomic-scale frictional characteristics of atomically thin 2D materials under different load were explored at different velocity using atomic force microscopy. The evolution of contact quality and puckering forming play important role in atomic-scale frictional characteristics of 2D materials. The critical load was proposed for the strengthening effect at transient period of atomic-scale friction. The velocity-dependent evolution of contact quality affects the strengthening effect when the normal load is less than the critical load. Strengthening degree and distance increase with the increase of the normal load because of high puckering and strong interfacial bonding when the load exceeds the critical load. The suspended 2D materials on asperities of rough substrate possess stronger strengthening effect than smooth substrate because of large deformation space and flexibility. The stick time in stick-slip behavior elongated with the increase of load as the lattice of 2D materials on rough substrate is locally distorted by large deformation under high load. The correlation between the strengthening effect and friction of 2D materials could potentially provide deep insights into the tribological behavior of atomically thin 2D materials. Graphical abstract: Image 1